PEMBERDAYAAN MASYARAKAT DALAM IMPLEMENTASI CORPORATE SOCIAL RESPONSIBILITY PT. SIDO MUNCUL (Studi Kajian Program Desa Rempah di Kabupaten Semarang) - Fuad Setyo Budi; Sulistyowati . .; Nunik Retno Herawati (Journal of Politic and Government Studies, 2017)
COMMUNITY EMPOWERMENT IN IMPLEMENTATION OF CORPORATE SOCIAL RESPONSIBILITY PT. SIDO MUNCUL(Studies Review of Herbal Village Program in Semarang District)FUAD SETYO BUDIDEPARTMENT OF POLITIC AND GOVERNMENTFACULTY OF SOCIAL AND POLITICAL SCIENCESDIPONEGORO UNIVERSITYABSTRACKCommunity development in the era of globalization today is no longer the responsibility of government alone. Private parties in this case the company has the same responsibility as well in the development and welfare of society. PT. Sido Muncul as a national company in Indonesia participated in the development of society through corporate social responsibility by making a Herbal Village Program by using the concept of empowerment are implemented in the district of Semarang.Type of this research is descriptive analytical through qualitative approach. Sources are found from primary data that is through interviewing the informant or key person by purposive sampling technique. Meanwhile, the secondary data comes from documents, archieves and other sources which relate to this research. The data was collected through observation, interviews, documentation and literature. Meanwhile analysis technique which is used in this research is qualitative analysis data by analyzing in the form of essay, description and conclusion of indication which is researched.The results of this study found that people are not involved in planning of the program. Public interest in the Herbal Village Program low because social and environmental conditions that are less supportive. Empowerment method used is socialization and training. Community participation in the empowerment initiative shown by the board of making organization of Herbal Village program, composting, participation in the form of cash grants, and participation in the program evaluation. In addition the research also found that in 2016 only two of the six target villages still carrying out development activities that is Gondoriyo village and Bergas Kidul village. The Herbal Village Program is the result of CSR’s PT. Sido Muncul that has defensive characteristics.Keywords: Community Empowerment, Corporate Social Responsibility